2007
DOI: 10.1080/15216540701242508
|View full text |Cite
|
Sign up to set email alerts
|

Biological hydroperoxides and singlet molecular oxygen generation

Abstract: SummaryThe decomposition of lipid hydroperoxides (LOOH) into peroxyl radicals is a potential source of singlet molecular oxygen (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
86
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 30 publications
0
86
0
10
Order By: Relevance
“…Peroxidation might result from direct assault of membrane lipids by ROS. Importantly, termination reactions between such hydroperoxyls result in the production of singlet oxygen (Miyamoto et al, 2007). In addition, specialized enzymes such as lipoxygenases and cyclooxygenases have also been implicated in singlet oxygen production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peroxidation might result from direct assault of membrane lipids by ROS. Importantly, termination reactions between such hydroperoxyls result in the production of singlet oxygen (Miyamoto et al, 2007). In addition, specialized enzymes such as lipoxygenases and cyclooxygenases have also been implicated in singlet oxygen production.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation, a source of singlet oxygen, occurs when a membrane component such as fatty acid undergoes oxidation (Miyamoto et al, 2007). Peroxidation might result from direct assault of membrane lipids by ROS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] Several photochemical and nonphotochemical reactions have been shown to produce singlet oxygen in biological systems. 22,24,26,27 In previous studies, we have demonstrated that biologically relevant hydroperoxides, such as lipid hydroperoxides, generate singlet oxygen in the presence of metal ions, peroxynitrite and hypochlorous acid. [27][28][29][30] In the present study, we have investigated whether cyt c-CL interaction could induce the generation of singlet oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…22,24,26,27 In previous studies, we have demonstrated that biologically relevant hydroperoxides, such as lipid hydroperoxides, generate singlet oxygen in the presence of metal ions, peroxynitrite and hypochlorous acid. [27][28][29][30] In the present study, we have investigated whether cyt c-CL interaction could induce the generation of singlet oxygen. Chemical trapping and luminescence measurements at 1270 nm clearly showed the generation of singlet oxygen in cyt c incubation with CL liposomes.…”
Section: Introductionmentioning
confidence: 99%